Risks and Threats in the Journalism Profession in Spain: Stress and Its Prevalence Factors - Herrero-Jiménez, Beatriz; Rodríguez-Crespo, Carlos; Berganza, Rosa (Anàlisi, 2025)
Various international programs currently focus on the psychosocial risks affecting the journalism profession, with stress being a prominent concern. However, there is little empirical evidence available to provide a comprehensive diagnosis of the situation. In this article, based on the holistic global safety model proposed by Slavtcheva-Petkova et al. (2023), and through a representative survey of Spanish journalists, the main threats identified as stress factors in the journalism profession are analyzed at three levels (micro, meso, and macro). The results show a statistically significant relationship between stress levels and gender, although the meso level is the best predictor of stress factors, in terms of professional routines and workloads. Additionally, digitalization also impacts the prevalence of stress.